2016
DOI: 10.1111/jth.13189
|View full text |Cite
|
Sign up to set email alerts
|

The role of ADAMTS‐13 activity and complement mutational analysis in differentiating acute thrombotic microangiopathies

Abstract: Essentials Molecular diagnostics has improved the differentiation of acute thrombotic microangiopathys (TMAs). Atypical hemolytic uremic syndrome may have features mimicking thrombotic thrombocytopenic purpura. We identified novel complement mutations and a high incidence of CD46, with favorable long term outcomes. Complement mutation analysis in TMA where the diagnosis is unclear and ADAMTS‐13 activity is >10%. SummaryBackgroundDifferentiation of acute thrombotic microangiopathy (TMA) at presentation has hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 55 publications
(92 reference statements)
1
24
0
8
Order By: Relevance
“…Thus far, complement-targeted therapies have only been explored in one case study of TTP with favourable outcome 114,127 . Of note, however, the clinical distinction between aHUS and TTP remains challenging in some cases, and individual patients may have clinical signs of both TTP and aHUS 128,129 ; more research is needed to elucidate the effect of complement on TMA beyond aHUS.…”
Section: Complement-mediated Kidney Diseasementioning
confidence: 99%
“…Thus far, complement-targeted therapies have only been explored in one case study of TTP with favourable outcome 114,127 . Of note, however, the clinical distinction between aHUS and TTP remains challenging in some cases, and individual patients may have clinical signs of both TTP and aHUS 128,129 ; more research is needed to elucidate the effect of complement on TMA beyond aHUS.…”
Section: Complement-mediated Kidney Diseasementioning
confidence: 99%
“…1ve, positive; AAV, ANCA-associated vasculitis; Ab, antibody; ACA, anticentromere antibody; ACEI, angiotensin-converting enzyme inhibitor; ADAMTS13, a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13; Ag, antigen; aHUS, atypical hemolytic uremic syndrome; ANA antinuclear antibody; anti-ds DNA, antidouble-stranded DNA; anti-Scl70, anti-topoisomerase I antibody; BMT; bone marrow transplant; C3G, C3 glomerulopathy; CAPS, catastrophic antiphospholipid syndrome; DGKE, gene encoding diacylglycerol kinase «; DIC, disseminated intravascular coagulation; FH, factor H; FI, factor I; Hb, hemoglobin; HUS, hemolytic uremic syndrome; LDH, lactate dehydrogenase; MAHA, microangiopathic hemolytic anemia; MN, membranous nephropathy; MPGN,membranoproliferative GN; PE, plasma exchange; SRC,scleroderma renalcrisis; STEC, shiga toxin-producing Escherichia coli;Stx, shiga toxin; T-Ag, Thomsen-Friedenreich antigen; TMA, thrombotic microangiopathy; TTP, thrombotic thrombocytopenic purpura. reportedly more severe thrombocytopenia (,30310 9 /L) and less severe AKI (serum creatinine, 1.7-2.3 mg/dl) (45), but these are not absolute and should not be relied upon in clinical practice (10), where the diagnosis is confirmed by ADAMTS13 activity ,10% (5). TTP was historically almost universally fatal, but after the introduction of PE treatment, mortality decreased to ,10% (46).…”
Section: Thrombotic Thrombocytopenic Purpuramentioning
confidence: 99%
“…delirium, seizures). It has been suggested that more severe thrombocytopenia (platelet count <30 × 10 9 /L) and milder renal impairment (serum creatinine <200 μmol/L) may help to distinguish TTP from aHUS but these criteria are neither sensitive nor specific . Rather, TTP is defined by severely reduced (<10%) activity of the von Willebrand factor (vWF)‐cleaving protease, ADAMTS13.…”
Section: Causes Of Tmamentioning
confidence: 99%